2018
DOI: 10.1021/acs.joc.8b00028
|View full text |Cite
|
Sign up to set email alerts
|

Samholides, Swinholide-Related Metabolites from a Marine Cyanobacterium cf. Phormidium sp.

Abstract: Cancer cell cytotoxicity was used to guide the isolation of nine new swinholide-related compounds, named samholides A–I (1–9), from an American Samoan marine cyanobacterium cf. Phormidium sp. Their structures were determined by extensive analysis of 1D and 2D NMR spectroscopic data. The new compounds share an unusual 20-demethyl 44-membered lactone ring composed of two monomers, and they demonstrate structural diversity arising from geometric isomerization of double bonds, sugar units with unique glyceryl moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…An alternative production method is based on the rationale that BGCs are subject to extensive horizontal gene transfer and that culturable sources therefore likely exist even for idiosyncratic compounds from deep-branching, uncultured divisions. Previous work on the serendipitous discovery of culturable bacterial producers of invertebrate polyketides [36][37][38][39] support this concept. As shown here, a targeted, BGC-based search can not only reveal such producers, but also yield novel synthetic biology chassis for previously demanding biosynthetic steps.…”
Section: Resultsmentioning
confidence: 92%
“…An alternative production method is based on the rationale that BGCs are subject to extensive horizontal gene transfer and that culturable sources therefore likely exist even for idiosyncratic compounds from deep-branching, uncultured divisions. Previous work on the serendipitous discovery of culturable bacterial producers of invertebrate polyketides [36][37][38][39] support this concept. As shown here, a targeted, BGC-based search can not only reveal such producers, but also yield novel synthetic biology chassis for previously demanding biosynthetic steps.…”
Section: Resultsmentioning
confidence: 92%
“…Methods for the NCI-H460 cytotoxicity assay [ 101 ] and the Griess assay [ 102 , 103 ] were adapted from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…All of these samholides showed potential activities against the human lung cancer cell line H-460 with IC 50 values ranging from 170 to 910 nM. Comparison of the activities of these samholides suggested that the sugar and glycericacid units played important roles in enhancing the cytotoxic activity (Tao et al, 2018).…”
Section: Macrocyclic Lactonesmentioning
confidence: 99%